Uma trajetória submersa: a “hipótese Nietzsche” de Michel Foucault em seus cursos no Collège de France entre 1970 e 1976 - Dias, Rafael Gironi (2022)
The fragmented genealogies performed by Foucault in the first half of the 1970s are marked by the arrhythmia of discontinuities, and the analysis of events, often diluted with the dust of history, its privileged sources. In this context, the philosopher elaborates a working hypothesis that aims to combine the critique of discursive events from the archaeology of knowledge, with a genealogy that displays the marks of power in the constitution of realities from a discourse of truth; that is, a Nietzsche hypothesis about the will to know and the will to power. With the objective of verifying the construction of this hypothesis from its methodological operators, with emphasis on the notion of event, the study followed Foucault's genealogical trajectory through his courses held at the Collège de France from his inaugural class, The Discourse of Language (L'Ordre du discours), till the course of 1976, Society Must Be Defended (“Il faut défendre la société”). Thus, the genealogies undertaken by the philosopher in this period, instead of constituting models for an analytical of power in its various forms, they allow to recover the "materiality of the discourse", a central element to understand the relations of power and knowledge in Western societies, and they mainly enable the creation of necessary counter-knowledge for struggles and confrontations in what is currently intolerable.